Chapter Measuring the impact of healthcare indicators on academic medical centers' scientific production - Cuccurullo, Corrado (Proceedings e report, 2021)
The Italian public-owned Academic Medical Centers (AMCs) are hospitals where the activities of scientific research, teaching, and patients care are fully integrated. AMCs have an enormous impact on society and country health. Recently, policymakers and practitioners give more and more great importance to the AMCs' scientific activity for both welfare and national competitivity. The scientific production and its impact on the research community could be obviously affected by different factors related to the structural and operational characteristics of each AMC. Healthcare institutions could be different for the typology of services that they offer, their geolocation, the presence/absence of Emergency Departments, the number of employees, and so forth. In this sense, our study aims to investigate and determine which are the possible factors impacting the research productivity of AMCs. We develop a model to assess the academic value of AMCs by taking into account these factors and how they are related to healthcare performance, measured in terms of scientific production (e.g. scientific publications) and impact on the research field (e.g. citations). To face this issue, for each of the public AMCs we collect data about research productivity from bibliographic indexing databases (e.g. Web of Science, PubMed) and we retrieve structural information mainly from their official websites. This work has been partially financed by the research project "Leading Change in Academic Medical Centers", funded by the competitive call for projects V:ALERE 2019. The project aims to provide evidence, advice, and remarks to help the agents of the public health system to address the many challenges that they face.